SUMMIT-07: a randomized trial of NKTR-181, a new molecular entity, full mu-opioid receptor agonist for chronic low-back pain. Issue 6 (June 2019) - Markman, John; Gudin, Jeffrey; Rauck, Richard; Argoff, Charles; Rowbotham, Michael; Agaiby, Eva; Gimbel, Joseph; Katz, Nathaniel; Doberstein, Stephen K.; Tagliaferri, Mary; Lu, Lin; Siddhanti, Suresh; et al.
Abstract : Abstract: NKTR-181, a new molecular entity, mu-opioid receptor agonist with an inherently slow rate of central nervous system (CNS) entry, was designed to provide analgesia while reducing abuse potential. This phase 3, enriched-enrollment, randomized-withdrawal trial evaluated the analgesic efficacy, safety, and tolerability of NKTR-181 in patients with chronic low-back pain (CLBP). Adults with moderate-to-severe CLBP refractory to nonopioid analgesics achieving an analgesic NKTR-181 dosage (100-400 mg twice daily) during the open-label titration period were randomized to continued NKTR-181 treatment, double-blind, or switched to placebo. The study was conducted at 55 sites in the United States. Of 1189 patients exposed to NKTR-181 during the titration period, 610 were randomized to NKTR-181 100 to 400 mg every 12 hours or placebo for 12 weeks. The primary outcome measure was change in weekly pain score (scale, 0-10) at 12 weeks from randomization baseline. Secondary outcome measures included responder rates defined by ≥30% and ≥50% improvement in pain score from screening to 12 weeks. Among 610 randomized patients, the mean pain score decreased from 6.73 to 2.32 during open-label titration. After randomization, the least-squares mean change in pain score was +0.92 for NKTR-181 vs +1.46 for placebo ( P = 0.002). The ≥30%-improvement responder rate of NKTR-181 vs placebo was 71.2% vs 57.1% ( P < 0.001), and the ≥50%-improvement responder rate was 51.1% vs 37.9% ( P = 0.001). NKTR-181 was well tolerated with a low incidence (<3%) of CNS-related adverse events during the randomized treatment phase. In patients with moderate-to-severe CLBP, NKTR-181 demonstrated significant analgesic efficacy and a favorable safety/tolerability profile, with a low incidence of CNS adverse events. Abstract : Supplemental Digital Content is Available in the Text.NKTR-181 provides effective analgesia in patients with moderate-to-severe chronic low-back pain with low incidence of central nervous system side effects.